2016
DOI: 10.1007/s40618-016-0552-3
|View full text |Cite
|
Sign up to set email alerts
|

Who has the worst attitudes toward sexual minorities? Comparison of transphobia and homophobia levels in gender dysphoric individuals, the general population and health care providers

Abstract: Participants completed the Modern Homophobia Scale (MHS) and the Attitudes Toward Transgendered Individuals Scale (ATTI) in order to assess attitudes toward gay men and lesbian women and toward transgender individuals, respectively. In addition, GDs completed the Gender Identity/Gender Dysphoria Questionnaire (GIDYQ-AA) and ATTI to measure, respectively, gender dysphoria levels and internalized transphobia. Religious attitudes were evaluated by means of the Religious Fundamentalism Scale (RFS), and Discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 74 publications
5
56
1
6
Order By: Relevance
“…This finding is in line with research findings put forth by Fisher et al (2017), who studied the attitude of men and women toward sexual minorities and found that cisgender men showed significantly higher levels of transphobia than cisgender women. In that study, the authors described how cisgender men experienced the transition of transgender individuals as an impairment of their own masculinity (Fisher et al, 2017); they may see transgender people as a threat, and the devaluation of transgender people is a response to that threat (Norton & Herek, 2013). In this study, most participants reported openness and integration in society, which are characteristics referring to the post-transition stages of Devor (2004).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in line with research findings put forth by Fisher et al (2017), who studied the attitude of men and women toward sexual minorities and found that cisgender men showed significantly higher levels of transphobia than cisgender women. In that study, the authors described how cisgender men experienced the transition of transgender individuals as an impairment of their own masculinity (Fisher et al, 2017); they may see transgender people as a threat, and the devaluation of transgender people is a response to that threat (Norton & Herek, 2013). In this study, most participants reported openness and integration in society, which are characteristics referring to the post-transition stages of Devor (2004).…”
Section: Discussionsupporting
confidence: 92%
“…The GAPS is a 30-item scale designed to measure health practitioners' beliefs and behaviors regarding care of gay and lesbian individuals. The instrument uses a 5-point Likert scale from strongly agree (5) to strongly disagree (1) for items 1-15 and from always (5) to never (1) for items [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The directionality and scoring for items were retained from the original instrument with the neutral answer option shifted to the far right to allow for a genuine non-response option as with the prior two scales.…”
Section: Gaps 34mentioning
confidence: 99%
“…[4][5][6][7][8] Past studies have suggested that more SGM-speci c health training, 5,9,10 personal and professional experiences with SGM people, [11][12][13][14] and certain sociodemographic factors are associated with increased clinician competence in caring for SGM patients. [15][16] Speci cally, identifying as lesbian, gay, bisexual, transgender, or queer (LGBTQ); female sex-assigned-at-birth; [17][18][19][20][21][22][23][24][25][26] liberal political a liation; 21,22,27 less religiosity; 9,14,22,28 and less spirituality 29 have predicted more a rming attitudes toward SGM people. Also, younger age, 10 white (versus non-white) race, 18,20,26 and less conservative religion, 9,21,30 have predicted less bias toward SGM people in past samples.…”
Section: Introductionmentioning
confidence: 99%
“…This study sought to explore the processes surrounding proxy response to SOGI questions. Because LGBT individuals have experienced social stigma in the United States, SOGI questions may elicit more privacy and confidentiality concerns compared to other questions typically included on federal surveys (Fisher et al 2017;SMART Report 2009;GenIUSS Group 2014). These privacy and confidentiality concerns may cause respondent reluctance to self or proxy report SOGI on a federal survey, or to not disclose their status to other household members, creating difficulties in proxy response.…”
Section: Motivationmentioning
confidence: 99%